Detection And Identification Of Circulating Toxoplasma Gondii Antigens And Host Specific Proteins In Toxoplasmosis Via Serum Proteomic Approach - Osman, Emelia (2010)
Toxoplasma gondii is an intracellular parasite of world-wide distribution. Infection in pregnant women may result in abortion and foetal abnormalities, and may be life-threatening in immunocompromised hosts. Many studies have been performed on developing an antigen detection assay for T. gondii. However, such assay is unavailable commercially, one reason may be due to lack of good data regarding Toxoplasma circulating antigens in the blood of actively infected individuals. Proteomics has greatly aided in discovery of disease infection markers for diagnostic purposes, thus this approach was used in this study to identify potential serum infection markers in toxoplasmosis. Initially, an ELISA employing monoclonal anti-Toxoplasma SAG1 (p30) as the capture antibody to detect T. gondii circulating antigens in serum samples was developed. Subsequently a study on protein profiles of serum from Toxoplasma gondii infection using two dimensional electrophoresis (2-DE) was performed, followed by identification and characterization studies of the circulating T. gondii proteins and host specific proteins in the serum samples of active toxoplasmosis patients by Western blot and mass-spectrometry analysis.